2020
DOI: 10.2183/pjab.96.005
|View full text |Cite
|
Sign up to set email alerts
|

Advances in gravity analyses for studying volcanoes and earthquakes

Abstract: This report highlights the usefulness and applicability of various gravimetric methods for studying earthquakes and volcanic activities. A high-resolution gravity anomaly map of Japan reveals areas with very steep horizontal gradients, where potential seismic faults are likely to be buried. Such traditional geoprospecting is coupled with novel cosmic-ray radiography to produce a fine-resolution (<100 m) three-dimensional density structure of a volcano. On the other hand, temporal gravity changes provide invalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…We can mention for instance the difficulty of separating post-glacial rebound effects from present-day ice-melting where the combination of AG and SG observations helped considerably to reduce the uncertainty in the AG estimated decrease due to ice melting in Svalbard (Memin et al 2014). Furthermore, studies on slow recharge processes in magma chambers could benefit greatly from a thorough knowledge of the drift of the gravimeters used to monitor active volcanoes (Okubo, 2020 ; Riccardi et al, 2008 ). Knowledge of the purely instrumental noise and separation from environmental noise can help to detect small signals which are hidden in the overall noise (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We can mention for instance the difficulty of separating post-glacial rebound effects from present-day ice-melting where the combination of AG and SG observations helped considerably to reduce the uncertainty in the AG estimated decrease due to ice melting in Svalbard (Memin et al 2014). Furthermore, studies on slow recharge processes in magma chambers could benefit greatly from a thorough knowledge of the drift of the gravimeters used to monitor active volcanoes (Okubo, 2020 ; Riccardi et al, 2008 ). Knowledge of the purely instrumental noise and separation from environmental noise can help to detect small signals which are hidden in the overall noise (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Since most dike/sheet injections do not result in eruptions (Gudmundsson 2020), a more fruitful approach might be to look for evidence of earthquake-triggered dike/sheet injections rather than eruptions. Advances in muography, magnetotelluric and gravimetric techniques will allow further constraints on volcanotectonic structures that can be linked to field measurements (Athanassas 2020;Pearce et al 2020;Okubo 2020). Also, global satellite-measured precipitation will help to understand how infiltrated rain/ground water affect volcanoes under unrest (Farquharson and Amelung 2020).…”
Section: Volcanotectonics In 2030mentioning
confidence: 99%
“…Spatiotemporal gravity signals from gravity measurement have contributed to the understanding of the surface and subsurface mass redistribution, which re ects the crustal deformation and density changes (Van camp et al, 2017; Battaglia et al, 2018). In the past few decades, the satellite and terrestrial gravity data have been employed to investigate the geophysical process of earthquake (Tanaka et al, 2010;Okubo et al, 2020;Bouih et al, 2022). Recently, it is reported that the gravity changes derived from satellite gravity measurements may be connected to the pre-seismic signals potentially caused by the deep mass redistribution of the large subduction earthquakes, such as the 2010 M w 8.8 Maule earthquake (Bouih et al, 2022) and the 2011 M w 9.0 Tohuku-Oki earthquake (Panet et al, 2018(Panet et al, , 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to satellite gravity observation, the Terrestrial Hybrid Repeated Gravity Observation (THRGO) system (Hinderer et al, 2016;Okubo et al, 2020) can solve the problem of spatial limitation. In this system, the microgal-level (1 microgal = 1 µGal = 10 − 8 m/s 2 ) absolute and relative gravity observations can be periodically performed in local areas.…”
Section: Introductionmentioning
confidence: 99%